Pengaruh Implementasi Kurikulum Keterampilan terhadap Kompetensi Siswa di MA PK Al-Hikmah Kota Tasikmalaya - Handayani, Multhia; Komalasari, Imas; Resnasari, Upi Luthfiah (Institut Nahdlatul Ulama Tasikmalaya, 2024)
The curriculum is the heart of education that needs to be implemented in educational institutions as optimally as possible because it has an impact on student learning outcomes. Optimal learning outcomes are in essence related to the curriculum used, including skills programs that equip students with skills that are tailored to their interests and abilities, as well as life coaching in the form of expertise or skills for students when they leave educational institutions. This study aims to determine the implementation of the skills curriculum, student competence and how much influence the implementation of the skills curriculum has on student competence. The method used is a survey method with a quantitative approach with a sample of 20 MA PK Al-Hikmah Tasikmalaya teachers through a questionnaire. The results of the analysis show that the implementation of the skills curriculum at MA PK Al-Hikmah Tasikmalaya City in accordance with the indicators in the Decree of the Minister of Religion (KMA) 184 is in the very good category with an average score of 3.512. Student competence consisting of cognitive, affective and psychomotor is in the good category with an average value of 3.246. The positive effect of Skills Curriculum Implementation on Student Competence with a regression value of 0.700 with a significant level of 0.001. Implementation of the Skills Curriculum contributes 49% to Student Competence, the remaining 51% is influenced by other variables. The implication for educational institutions, the implementation of the skills curriculum will be able to create good student competence.